A neutron diffuse scattering study of PbZrO3 and Zr‐rich PbZr1–xTixO3. (3rd December 2015) - Zhang, Nan; Paściak, Marek; Glazer, A. M.; Hlinka, Jirka; Gutmann, Matthias; Sparkes, Hazel A.; Welberry, T. R.; Majchrowski, Andrzej; Roleder, K.; Xie, Yujuan; Ye, Zuo‐Guang
Abstract : A combined neutron diffuse scattering study and model analysis of the antiferroelectric crystal PbZrO3 is described. Following on from earlier X‐ray diffuse scattering studies, supporting evidence for disordering of oxygen octahedral tilts and Pb displacements is shown in the high‐temperature cubic phase. Excess diffuse scattering intensity is found at the M and R points in the Brillouin zone. A shell‐model molecular dynamics simulation closely reproduces the neutron diffuse scattering pattern. Both in‐phase and antiphase tilts are found in the structural model, with in‐phase tilts predominating. The transition between disordered and ordered structure is discussed and compared with that seen in Zr‐rich PbZr1− x Ti x O3 .